Cost and supply considerations for antibody therapeutics - Chun Chen; Zoe Garcia; David Chen; Hong Liu; Piper Trelstad (mAbs)
Monoclonal antibodies (mAbs) and mAb-derived biologics have achieved substantial success across various therapeutic areas over recent decades. Their widespread adoption, however, remains constrained due to high prices and challenges in supply. Here, we examine the general price and cost structure of mAbs and mAb-derived therapeutics and identify directions to improve affordability and strategies to ensure supply. Mainstream and emerging biomanufacturing formats and their implications on cost and supply are discussed. We also summarize modeling tools used across industry for process economics analysis, emphasizing the importance of this assessment throughout the product development lifecycle. A comprehensive understanding of cost and supply scenarios will empower industry players to thrive despite competition, navigate supply challenges, and broaden access to mAb therapeutics for more patients.